FROM ENGLISH PLUS TO ENGLISH 1 AND 2: ASSESSING TRANSFER OF GRAMMAR SKILLS - Bartolata, Jocelyn I.; Meneses, Ma. Celina Eladia G. (PEOPLE: International Journal of Social Sciences, 2016)
This paper explores the effectiveness of grammar skills transfer from English Plus to English 1 & 2. English Plus is meant to address the English Language deficiency of incoming freshmen by providing them enabling skills to cope with college. It aimed to address the lack of readiness of entrants, through the improvement of crucial language skills, particularly grammar and usage. The research used the descriptive-evaluative method. It was anchored on the Constructivist’s Paradigm: “individuals construct new knowledge from their experiences, either by accommodation or assimilation (Microsoft Encarta,2007”) It was found out that nowhere in the evaluation did it appear that the English Plus takers even approximated the competencies of the non-takers. This means that English Plus has in fact no carry-over effect on students taking English 1 and 2. This means further that English Plus takers were NOT able to integrate or apply learning of English grammar in this college course as evidenced by the disparity in the scores of the two sets of respondents. It is therefore recommended that specific measures be undertaken to improve the implementation of the English Plus – to provide coping skills and to ensure that there is indeed assimilation of learning.